Finite element stress and failure analysis of railway track structural system - Liu, Zhufeng (Nanyang Technological University, 2022)
Railway track comprises of continuous welded rail mounted with rail clips on sleepers integrated to a ballast or concrete slab track form system. Thermite weld is an important structural component connecting rail steel segments to form a continuous track structure and the rail clip fastening system provides flexibility and turnover resistance for running rails. The failure of rails and rail clips compromises the structural integrity in the railway track system which can lead to unplanned downtime and possible safety issues such as derailment in railway operations. The objective of this research is to study the fatigue failures of the thermite weld and rail clips subjected to train wheel-induced dynamic loadings. Under complex multiaxial loadings in service, head-to-web, web-to-foot and rail foot regions along the weld edge of thermite weld and arch regions of rail clips are susceptible to fatigue crack formation. In this research, a fatigue assessment methodology integrates the experiment work and finite element modeling work leading to fatigue life prediction models for the thermite weld and rail clip failures. Firstly, the mechanical and fatigue properties of rail and clip steels were investigated through a series of experimental studies. On-site wireless strain measurement was also conducted to record the train wheel-induced strain spectrum at a thermite weld of a sharp curve in a metro tunnel. Secondly, a three-dimensional finite element (FE) model for railway track system including the thermite weld and rail clips was developed by using an implicit-explicit sequence analysis to investigate the stress states at the regions of interest. The model was validated by a train roll-in test and a good consistency is observed between the simulation results and field measurements. Lastly, a time-efficient fatigue analysis methodology was proposed with the smallest enclosing circle algorithm implemented to search the critical plane orientations and calculate the maximum fatigue parameter for performing multiaxial fatigue analysis. The fatigue damage and crack initiation life of the thermite weld and rail clips were predicted according to stress-based and strain-based fatigue models. The fatigue assessment methodology developed for the thermite weld and rail clips provides a comprehensive and rapid evaluation of the failures observed in the railway track system. The influence of change in material, geometry, loading conditions, and track structures on fatigue life can also be evaluated in a short period.